Factors Influencing Team Performance: A Case Study of Teachers in Three Vocational Colleges in Weifang, Shandong Province, China - Zhao , Xiaoxuan; Chotipiboonsub, Jareeporn; Vongchavalitkul, Busaya; Reangsuwan, Ati (International Journal of Sociologies and Anthropologies Science Reviews, 2024)
Background and Aims: With the development of today’s social economy and China’s economy and society, the status of vocational education in China is getting higher and higher, but at the same time, the requirements for teachers are gradually increasing. The purpose of this study was to clarify cooperation, reward, trust team cohesion, and team performance and to investigate the factors influencing team performance. Material and Method: The questionnaires were distributed to 325 teachers from three vocational colleges in Weifang, Shandong Province, China, who participated in the questionnaire. Statistical analysis includes descriptive analysis, correlation analysis, and regression analysis. Results: The findings revealed that cooperation, team cohesion, reward, and trust exert positive influences on teachers’ team performance. Conclusion: Based on these results, the study recommends implementing measures such as fostering team cooperation, strengthening team cohesion, providing reasonable rewards, and instilling full trust to effectively enhance teacher team performance within the context of production-education integration.